Linking Place and Mind: Localness As a Factor in Socio-Cognitive Salience - Jensen, Marie M. (Frontiers in Psychology, 2016)
This paper investigates the salience of vernacular Tyneside forms on the basis of theories of enregisterment and exemplar processing. On one level, exemplar theory provides a psycholinguistic account of how the link between social value and linguistic features is possible. Conversely, integrating the notion of social value into exemplar theory extends the value of this originally cognitive theory to social domains. It is suggested that the association of social value and particular local, linguistic forms may contribute to the salience of these forms among local speakers. The empirical work reported here takes the form of a questionnaire study, which aims to uncover Tyneside inhabitants’ awareness of forms as well as their affiliation with the local community. Results showed differences in frequency perceptions between participants themselves and others which indicate that speakers can identify local forms as such, but that the variety is stigmatized. The strength of local affiliation correlated with participants’ own language use and it is suggested that this can be accounted for by employing a social personae explanation, where speakers use certain salient forms to index local belonging despite overt stigma.